Utilization of Energy Sources, Financial Stability and Prosperity in the Economy of Indonesia - Hanh, Hoang Thanh; Huy, Dinh Tran Ngoc; Dat, Pham Minh (International Journal of Energy Economics and Policy, 2020)
The aim of this study was to explore the relationship between utilization of energy sources, financial stability and prosperity in the economy of Indonesia. For this purpose this study conducted panel data analysis and gathered data from 1990 to 2018. The study explored the relationship of CO2 emissions and utilization of energy sources per capita as indicators of utilization of energy sources. The indicators for financial stability were real domestic credit to the private sector where the financial information of different financial institutions operating in Indonesia has been collected. The prosperity in the economy indicator for Indonesia was Gross Domestic Product (GDP) per capita and also the labour force that works within different sectors operating in the country. Using descriptive statistics, Unit root analysis, and the autoregressive distributed lag (ARDL) techniques, a panel data analysis was conducted. The results of showed that there is long term relationship between utilization of energy sources, financial stability and prosperity in the economy indictors of Indonesia. Keywords: Financial Stability, Utilization of Energy Sources, Gross Domestic Product, Autoregressive Distributed Lag JEL Classifications: B26, O13 DOI: https://doi.org/10.32479/ijeep.10242